Development and validation of a LC-ESI-MS/MS method for simultaneous whole blood analysis of 51 new psychoactive substances - Franck, Maria Cristina; Goldnadel Monteiro, Maristela; Limberger, Renata Pereira (Drug Analytical Research, 2026)
In recent years, there has been a great increase in seizures and forensic analysis of new psychotropic substances (NPS) in the state of Rio Grande do Sul. The analysis of these compounds needs to be performed in biological samples in cases of violent deaths. A sensitive and reliable liquid chromatography-tandem mass spectrometry with electrospray ionization interface (LC-ESI-MS/MS) method was developed and validated for qualitative analysis of 51 NPS in whole blood forensic samples. Synthetic cathinones, phenethylamines, opioids, tryptamines, synthetic cannabinoids, and other hallucinogens and stimulants were included in the method. The validation parameters assessed were speciﬁcity, limit of detection, retention time precision, and matrix effect. Drug free pools (n=6) were used for validation, including post mortem samples as well as from living individuals. Adulterants, pharmaceuticals, metabolites, and other illicit drugs, totalling 39 compounds, were analyzed and no interference was noticed. The detection limits obtained were suitable for evaluation at recreational and non-fatal levels of consumption, mostly. The results revealed an appropriate matrix effect in 24 out of 51 substances tested, indicating the potential for future quantitative analysis with this method for these drugs. The developed and validated method is easy to implement, fast, with low cost, and suitable for use in routine forensic toxicology laboratory analysis.